2023
DOI: 10.1177/16878132231198338
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of the effects of non-Newtonian property of the solvent on particle suspension rheology

Naoki Masuyama,
Tomohiro Fukui

Abstract: To investigate the effects of the non-Newtonian properties of solvents on particle suspension rheology (non-Newtonian property and viscosity), we analyzed suspension flows with different solvent characteristics. We used the power-law model to express the non-Newtonian properties of solvents. The power-law index of the suspension was denoted as nsus. and that of the solvent as [Formula: see text] to distinguish between their non-Newtonian properties. Besides, to evaluate the non-Newtonian property of the partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In this study, in order to consider particle inertial effects, Reynolds number Re was set to 32, i.e., the particle Reynolds number Re p = 0.32. These are the same conditions as that of the previous study [12]. We used a circular rigid particle with a diameter of 2r as a suspended particle in this study.…”
Section: Computational Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, in order to consider particle inertial effects, Reynolds number Re was set to 32, i.e., the particle Reynolds number Re p = 0.32. These are the same conditions as that of the previous study [12]. We used a circular rigid particle with a diameter of 2r as a suspended particle in this study.…”
Section: Computational Modelmentioning
confidence: 99%
“…Concerning studies about rheology using non-Newtonian fluid, Tanaka et al [11] suggested that non-Newtonian properties of a solvent affected the relative viscosity and intrinsic viscosity of suspensions. Masuyama and Fukui [12] reported that a power-law fluid affects particle migration and rheological property in an inertial flow. As mentioned above, many studies have used a Newtonian fluid as a solvent, and power-law fluid has often been used in the studies about non-Newtonian fluid.…”
Section: Introductionmentioning
confidence: 99%